Contracts for the management of state-owned enterprises in the Ministry of Transport in the 1990s - Piotr Świątecki (Przegląd Komunikacyjny)
Abstract: A significant change was introduced to the legislation regulating the state-owned enterprises in the last decade of the 20th century. The change made it possible to transfer companies under control of different managerial entities on the basis of the so-called management contracts. In the following paper the author will give an account of the practices related to management contracts as concluded by the Ministry of Transport during the relevant period. Keywords: State-owned enterprise; Management contract; Transport